2001
DOI: 10.3758/bf03195738
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of short-term memory in complex mental calculation

Abstract: The aim of this study was to examine the involvement of the short-term memory system in complex mental addition by manipulating the phonological and visual similarity of two numbers to be added. The phonological similarity of the problems appeared to have a major effect on both speed and accuracy. However, the manipulation of visual similarity failed to have any measurable impact. This suggests that the phonological loop, rather than the visual-spatial sketch pad, would be used preferably for temporary storage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
70
1
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 21 publications
(28 reference statements)
10
70
1
4
Order By: Relevance
“…Decomposition of this interaction showed that this interaction completely bears on the presence of an executive load. These findings are consistent with previous research that also found that the central executive contributes to handling carries (e.g., Fürst & Hitch, 2000;Seitz & SchumannHengsteler, 2002), but they do not confirm previous findings that found a role for phonological effects in carrying (e.g., Ashcraft & Kirk, 2001;Noël et al, 2001;Seitz & SchumannHengsteler, 2002), and research that found no role for working memory in carrying (Logie et al, 1994).…”
Section: Load and Number Of Carriessupporting
confidence: 77%
See 2 more Smart Citations
“…Decomposition of this interaction showed that this interaction completely bears on the presence of an executive load. These findings are consistent with previous research that also found that the central executive contributes to handling carries (e.g., Fürst & Hitch, 2000;Seitz & SchumannHengsteler, 2002), but they do not confirm previous findings that found a role for phonological effects in carrying (e.g., Ashcraft & Kirk, 2001;Noël et al, 2001;Seitz & SchumannHengsteler, 2002), and research that found no role for working memory in carrying (Logie et al, 1994).…”
Section: Load and Number Of Carriessupporting
confidence: 77%
“…Logie et al (1994) did not observe differential effects of load on carry versus no-carry problems for either a phonological or a visuo-spatial load. In contrast, Noël, Désert, Aubrun, and Seron (2001) provided evidence for a mediation of the phonological loop in solving carry problems. They manipulated visual and phonological similarity of the digits to be added in additions of two three-digit numbers.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…More specifically, the recruitment of executive and phonological working memory increases as a function of the number of carry operations (Fürst & Hitch, 2000;Imbo, Vandierendonck, & De Rammelaere, 2007;Imbo, Vandierendonck, & Vergauwe, 2007;Noël et al, 2001). In the present experiment, we investigated whether the carry effect (i.e., the relative inefficiency on carry problems as compared to no-carry problems) differed across cultures.…”
Section: Working Memorymentioning
confidence: 99%
“…As for the relative frequency of strategy use, the efficiency of complex arithmetic strategies depends greatly on the presence of carry operations. Efficiency decreases when carry operations have to be performed (Hitch, 1978;Fürst & Hitch, 2000;Imbo, Vandierendonck, & De Rammelaere, 2007;Imbo, Vandierendonck, & Vergauwe, 2007;Logie, Gilhooly, & Wynn, 1994;Noël, Désert, Aubrun, & Seron, 2001). Interestingly, cultural differences in strategy efficiency have been shown in the domain of simple arithmetic.…”
mentioning
confidence: 99%